(untitled) (Enfield, NH., 2004)
This sequel to the earlier book entitled Drying Technology in Agriculture and Food Sciences, also edited by Arun S. Mujumdar, covers a broader spectrum of topics of current interest in dehydration of biological products ranging from biomass, enzymes, foods, grains, meat to wood. A panel of international experts have contributed their vast expertise and experience to make this book a valuable reference for academics as well as industry personnel involved in any aspect of preservation using dehydration techniques. This book includes indepth discussion of fundamental aspects, applications to drying of specific products and also reviews recent developments in dehydration technologies.
Keywords: Food; Drying